Characterisation of causative agents and pathological assessment of selected corn inbred lines against southern leaf blight disease in Malaysia - Kutawa, Abdulaziz Bashir (2016)
In Malaysia, corn is produced in small scale due to many diseases affecting this crop as a result of poor cultural practices or by planting susceptible hybrids to diseases. Leaf blight diseases have been identified as one of the main constraint for corn production in Malaysia. Yield loss could be up to 20-90%, if necessary disease management strategies were not employed, and this may leads to low income generation to the farmers. This research was carried out to characterize the causative agents of northern and southern leaf blight diseases in corn, and to assess resistance in selected inbred lines against southern leaf blight disease, as well as to determine the plant secondary metabolites produced during the interaction. Infected leaf samples were collected from infected farms of five major corn growing areas in Peninsular Malaysia from 2014 to 2015. A total of 15 isolates, were studied for their morphology. Based on morphological characteristics, the isolates were identified as Exserohilum turcicum and Cochliobolus heterostrophus. The conidial shapes for most of these pathogens were spindle, elongated and curved. Results of cultural characteristics showed that, the isolates varied in colony growth and colour. Colony growth rate of 15 isolates was significantly different at P ≤ 0.05 after being grown on three different media viz., potato dextrose agar (PDA), corn meal agar (CMA) and potato sucrose agar (PSA), where PSA showed the highest growth rate for southern leaf blight pathogen, while CMA was the highest for northern leaf blight pathogen and PDA media was the least for all the pathogens. Based on the colony colour, all the 15 isolates were grouped into five categories i.e. dark gray, light gray, gray, light to gray and gray to green. Based on colony growth, the 15 isolates were categorized into 3 groups‟ viz., poor restricted growth, moderate growth and profused growth. Result of conidial measurement indicated that, the number of septa ranged from 4-6 and 8-10 for isolates CH006 and CH004, respectively. The highest conidial length was 89.44 μm for isolates ET003 and the least isolate was CH006 with 44.12 μm. Likewise, the highest conidial width was 17.43 μm for isolates CH004 and the least were isolates ET002 and CH009 having 11.34 μm. Based on the pathogenicity test, isolate CH001 and CH009 shows the highest level of aggressiveness with disease severity index of 80% each, at the fourth week after inoculation. Isolate ET005 was found to be the least aggressive among the isolates tested, by having disease severity index of 22%. Molecular characterisation confirmed the identification of species, 10 of the isolates were C. heterostophus and 5 of the isolates were E. turcicum. Both the morphological and molecular identification have showed the same results. Results from assessment of resistance of selected inbred lines showed that, line SLBR5 was the most resistant line with mean disease severity index of 17.35%, while line SLBS3 was the most susceptible line by having mean disease severity 51.65%. The concentration of peroxidase (PO), polyphenols oxidase (PPO) and total phenolic content (TPC) were determined. In PO, a resistant inbred line, SLBR5 produced higher compounds with 6320, 7600 and 5800 mgGAE/g at 1st, 2nd and 3rd week after inoculation, respectively. Susceptible line, SLBS3 was found to produce less with 1640, 1800 and 1920 mgGAE/g at the same assessment periods. For PPO, inbred line SLBR5 was also found to produce higher PPO with 2440, 2560, and 2760 mgGAE/g at the 1st, 2nd and 3rd week after inoculation, respectively. While SLBS2 produced less PPO with 1080, 1240 and 880 mgGAE/g at the 1st, 2nd and 3rd week after inoculation, respectively. Similarly, in TPC, inbred line SLBR5 produced the highest TPC with 15720, 15960 and 17720 mgGAE/g at the 1st, 2nd and 3rd week after inoculation, respectively. Line SLBS3 was found to produce less TPC with 11960, 10240 and 10840 mgGAE/g at the 1st, 2nd and 3rd week after inoculation, respectively.